Pengaruh Kualitas Produk Terhadap Tingkat Kepuasan Pelanggan Studi Kasus Produk Wireline pada Penduduk Cisarua Bogor - Supariyani, Hj. Emmy; Fitriandi, Diki (Jurnal Ilmiah Ranggagading (JIR), 2009)
This research has purpose to know how are quality product the company established and its influence to customers satisfaction, and to know what factors have influence to wireline effectiveness and what efforts will be done. Based on ICSI (Indonesia Customer Satisfaction) survey to wireline produtct by PT Telkom, there are three criterions of customers satisfaction, namely satisfaction to product quality (Qualiti Satisfaction Score (QSS)) = 86,4%, Satisfaction to price (Value Satisfaction Score (VSS)) = 77,7%, and perpection thatâs used on the whole is the best product compared to other products (Percived Best Score) = 80,1%. From the result of simple correlation regression calculation, Itâs obtained simple regression equation, that is Y = 16,037 + 0,826 X. The result here shows that there is functional correlation between variable X (product quality) and variable Y (Customers Satisfaction Stage) will increase 0,826%. Whereas its correlation can be proven that, based on the calculation mentined above, there is positive and significant correlation as high as 0,614 between product quality and customers satisfaction stage, and the determination coefficient is R2 = 37,1%. Key words: Production quality; customers satisfaction